(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Approximate computing is a new paradigm for nanoscale technologies that overcomes the problem of mistake tolerance in computation, allowing for greater performance with less power. The 3-input MV is an important building component of majority logic (ML) in digital circuit design and is expected to play a significant role in numerous emerging nanotechnologies. In order to do this, the suggested multipliers and adders employ approximation compressors and a reduction circuitry that makes use of so-called complement bits.